2011
DOI: 10.1007/s00534-011-0419-0
|View full text |Cite
|
Sign up to set email alerts
|

Bile aspiration cytology in diagnosis of bile duct carcinoma: factors associated with positive yields

Abstract: In BDC patients with ENBD or PTCD, repeated BAC is useful, and six times was the optimum number of repeat samplings. Although the sensitivity of BAC is not sufficient for the preoperative diagnosis of malignant biliary stricture, the three independent factors noted above predict positive yields and indicate whether or not BAC should be repeated up to six times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 11 publications
2
11
1
Order By: Relevance
“…According to our previous analysis [10], positivity was lower in patients with ENBD than those with PTBD, perhaps because the collection volume was often smaller in the former, leading to a lower cellular yield. The bile cytology positivity per session was low, which was consistent with previous studies on exfoliative bile cytology [1][2][3][4][5][6][7][8][9]. However, this study demonstrated that positivity increased up to approximately 50% with repeat cytology.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…According to our previous analysis [10], positivity was lower in patients with ENBD than those with PTBD, perhaps because the collection volume was often smaller in the former, leading to a lower cellular yield. The bile cytology positivity per session was low, which was consistent with previous studies on exfoliative bile cytology [1][2][3][4][5][6][7][8][9]. However, this study demonstrated that positivity increased up to approximately 50% with repeat cytology.…”
Section: Discussionsupporting
confidence: 91%
“…Abdelghani et al. reported that papillary macroscopic tumor type was linked with higher positivity. Tumor cells of the protruding tumor type, compared to the sclerosing tumor type, may be more easily exfoliated, possibly leading to high sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although bile cytology is widely used for pathological confirmation of biliary and pancreatic tumors, its diagnostic efficacy is not satisfactory and may greatly vary depending on the level of proficiency of the cytopathologists or cytoscreeners when only the smear method is used . In contrast, the cell block (CB) method allows cytological and/or histological evaluation with hematoxylin‐eosin (HE) staining and with immunostaining for serial sections if necessary…”
Section: Introductionmentioning
confidence: 99%
“…A LTHOUGH BILE CYTOLOGY is widely used for pathological confirmation of biliary and pancreatic tumors, its diagnostic efficacy is not satisfactory and may greatly vary depending on the level of proficiency of the cytopathologists or cytoscreeners when only the smear method is used. [1][2][3][4][5][6][7][8][9][10][11][12] In contrast, the cell block (CB) method allows cytological and/or histological evaluation with hematoxylin-eosin (HE) staining and with immunostaining for serial sections if necessary. 13 We have previously reported the usefulness of the CB method using sodium alginate (SA) in patients who had undergone endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) 14 and pancreatic juice cytology.…”
Section: Introductionmentioning
confidence: 99%